THE ANNUAL CHANGES OF CPT OF TROLL LINE FISHERY IN PALABUHANRATU WEST JAVA, INDONESIA - Eflysa Aprilia; Asep Agus Handaka Suryana; Herman Hamdani; Alexander M.A Khan (Research Center for Fisheries, 2021)
Troll-line is one of the fishing gear, which categorized as a line-fishing with rod. Troll-line fishery in Palabuhanratu heavily depends on the installation of a deep-sea fish aggregating device (FADs). The deployment of FADs as a destined troll-liner’s fishing ground in southern Palabuhanratu, which geographically located at coordinates between 7o to 9o S and 104o to 106o E in the Indian Ocean. The FADs’ coordinates locations have been set in a portable handheld global position system (GPS) by fishers. This study provides new information on troll-liner catch-per-trip (CPT) based on fishers’ monthly data ranged from 2005-2018. The results showed that the highest catches were occurred between September to October every year with maximum catches rates was 1567, 2 kg/trip in February 2006 while the lowest was 174.10 kg/trip in August 2010. The average troll-liner catches from 2005-2018 was 740.33 kg/trip. Based on monthly catch data from 2005-2018, the highest CPT occurred in 2016.